High-Input Impedance Voltage-Mode Multifunction Filter with Four Grounded Components and Only Two Plus-Type DDCCs - Hua-Pin Chen (Active and Passive Electronic Components)
This paper introduces a novel voltage-mode multifunction biquadratic filter with single input and four outputs using two plus-type differential difference current conveyors (DDCCs) and four grounded passive components. The filter can realize inverting highpass, inverting bandpass, noninverting lowpass, and noninverting bandpass filter responses, simultaneously. It still maintains the following advantages: (i) using grounded capacitors attractive for integration and absorbing shunt parasitic capacitance, (ii) using grounded resistors at all X terminals of DDCCs suitable for the variations of filter parameters and absorbing series parasitic resistances at all X terminals of DDCCs, (iii) high-input impedance good for cascadability, (iv) no need to change the filter topology, (v) no need to component-matching conditions, (vi) low active and passive sensitivity performances, and (vii) simpler configuration due to the use of plus-type DDCCs only. HSPICE and MATLAB simulations results are provided to demonstrate the theoretical analysis.